PENGARUH ELECTRONIC WORD OF MOUTH DAN PRODUCT QUALITY TERHADAP PURCHASE DECISION SEPATU AEROSTREET DENGAN BRAND IMAGE SEBAGAI VARIABEL MEDIASI - Saputra, Maulid Tommy; Purmono, Bintoro Bagus; Jaya, Arman; Afifah, Nur; Setiawan, Harry (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
This study aims to examine the influence of electronic word of mouth and product quality on purchase decisions, with brand image as a mediating variable, in the context of Aerostreet shoe products. A quantitative approach was employed using purposive sampling, with a total of 231 respondents. Data were analyzed using SmartPLS version 4 with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results show that electronic word of mouth and product quality have a direct effect on both brand image and purchase decisions. Furthermore, brand image has a significant influence on purchase decisions. Additionally, electronic word of mouth and product quality indirectly affect purchase decisions through brand image. These findings highlight the important role of digital communication and product quality in shaping brand image and influencing consumer purchasing decisions, particularly for local brands such as Aerostreet.